Fiscal Strategy and Economic Growth: The Effect of Government Expenditure On Economic Growth in East Java Province - Elika Febrianti; Siti Rizqiyatul Munawaroh; Mei Ria Rahayu (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
The relationship between government spending and economic growth is a perennial topic of discussion and debate within a country's economy. A wealth of empirical evidence explores the causal relationship between these two macroeconomic variables and finds differing or contradictory results. This study aims to analyze the relationship between government spending and economic growth in East Java Province. This is done to determine whether the two influence each other or whether they are one-way. Panel data regression analysis was used to answer these analysis results. The data analyzed were annual panel data from 2011-2020. The results show that (i) the direct expenditure (BL) variable has a positive effect on the economic growth (PE) variable in East Java Province. (ii) the indirect expenditure (BTL) variable has a negative and significant effect on the economic growth (PE) variable in East Java Province. Based on the data analysis, it shows that there is a one-way causal relationship between direct expenditure (BL) and indirect expenditure (BTL) on economic growth (PE).